Non Steroidal Anti-Inflammatory Drugs and Inflammatory Bowel Disease - Amir Klein; Rami Eliakim (MDPI AG, 2010)
Inflammatory Bowel Diseases (IBD) are an immune mediated chronic or relapsing disorders of the gastrointestinal (GI) tract. IBD is characterized by a chronic intestinal inflammatory process with various components contributing to the pathogenesis of the disease including environmental factors such as smoking or use of Non Steroidal Anti-Inflammatory Drugs (NSAIDS). NSAIDS are among the most commonly used medications for the treatment of various inflammatory conditions. The main factor limiting NSAIDS use is the concern for the development of gastrointestinal toxicity including mucosal injury. A possible association between the use of NSAIDS and the onset or relapse of IBD has been repeatedly suggested. This article will review the current concepts and evidence of the relationship between IBD and NSAIDS.